Developing Higher Order Thinking Skills Test Instruments for English Speaking Classes: Sing a Song Material - Multazam Abubakar; Nurfatwa Putri Husain; Mardiana Mardiana (Universitas Sulawesi Barat, 2022)
This study aims at creating HOTS items for the